DEUTERATED OXYTOCINS: THE SYNTHESIS AND BIOLOGICAL PROPERTIES OF A CRYSTALLINE ANALOG OF DEAMINO-OXYTOCIN DEUTERATED IN THE 5-ASPARAGINE POSITION - Blomquist, Alfred T. (1969)
This paper describes the synthesis and biological activity of [5-L-asparagine-α,β,β-d(3)]-deamino-oxytocin. The model peptide S-benzyl-β-mercaptopropionyl-L- asparaginyl-α,β,β-d(3)-glycinamide was also prepared to observe the effect of the conditions of peptide synthesis on the deuterium content. It was found that normal synthetic procedures could be used without a significant loss in the deuterium content. The [5-L-asparagine-α,β,β-d(3)]-deamino-oxytocin had, within experimental error, the same avian vasodepressor and oxytocic activities as deamino-oxytocin itself.